Passive Intermodulation Measurement: Challenges and Solutions. (July 2022) - Cai, Zhanghua; Liu, Lie; de Paulis, Francesco; Qi, Yihong
Abstract: In modern wireless communication systems, the signal-to-noise ratio (SNR) is one of the most important performance indicators. When the other radio frequency (RF) performance of the components is well designed, passive intermodulation (PIM) interference may become an important factor limiting the system's SNR. Whether it is a base station, an indoor distributed antenna system, or a satellite system, there are stringent PIM level requirements to minimize interference and enhance network capacity in multicarrier networks. Especially for systems of high power and wide bandwidth such as 5G wireless communication, PIM interference is even more serious. Due to the complexity and uncertainty of PIM, measurement is the most important means to study and evaluate the PIM performance of wireless communication systems. In this review, the current main PIM measurement methods recommended by International Electrotechnical Commission (IEC) and other standard organizations are introduced, and several key challenges in PIM measurement and their solutions (including the design of PIM tester, the location of the PIM sources, the design of compact PIM anechoic chambers, and the evaluation methods of PIM anechoic chambers) are highlighted. These challenges are of great significance to solve PIM problems that may arise during device characterization and verification in real wireless communication systems.